PERBANDINGAN STRATEGI INKUIRI TERBIMBING DENGAN PROBLEM SOLVING TERHADAP PEMAHAMAN KONSEPTUAL DAN ALGORITMA SISWA DENGAN KEMAMPUAN BERPIKIR ILMIAH RENDAH - Priyasmika, Rendy (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2019)
AbstractOne of the high school chemistry materials that contains concrete concepts, abstracts andinvolves mathematical calculations is solubility and solubility product (Ksp). Conceptualunderstanding is usually expressed in short sentences while understanding algorithms isexpressed by mathematical equations. Both of these understandings are closely related to oneanother so that to teach them requires the right learning strategies. Guided inquiry learningstrategies and Problem Solving are thought to be able to improve the conceptual understandingand algorithm understanding of students with Low Scientific Thinking Ability. This study aimsto determine differences in conceptual understanding with algorithm understanding of studentswith KBIR that are taught with guided inquiry strategies and Problem Solving. This study usesa quasi-experimental design with posttest only control group design. Data from the conceptualunderstanding and algorithm test results obtained from the test using 20 multiple choicequestions with a reliability coefficient of 0.71 and content validity of 93.17%. Data analysisusing t test and Product Moment correlation at a significance level of 5%. The results show thatThe learning outcomes of student with low scientific thinking ability that learned by guidedinquiry’s strategy is higher than the students that learned by problem solving’s strategy and Theunderstanding of algorithms of students with low scientific thinking ability is higher thanconceptual understanding both of which that learned by guided inquiry strategies and problemsolving strategies.Keywords: guided inquiry, problem solving, conceptual understanding, algorithmunderstanding, scientific thinking ability